Mobilizing for Conservation: The Role of Social Movements in Damaran Baru Ecovillage, Indonesia - Hajad, Vellayati; Fadhly , Zuhrizal; Husna, Cut Asmaul; Ikhsan, Ikhsan; Setiawan, Deni (Forest and Society, 2025)
This article highlights the role of social movements in environmental conservation by developing an ecovillage in Damaran Baru in Bener Meriah Regency, Aceh, Indonesia, focusing on ecological sustainability and gender inclusivity. The primary aim of this paper is to explore how community-based social movements and government policies can collaborate to promote sustainable tourism practices that protect the environment and enhance local community welfare. A qualitative method with a phenomenological approach was employed in the data collection process, which included field observations, in-depth interviews with village residents and relevant stakeholders, and analysis of official and non-official documents related to the ecovillage program. The research findings show that Damaran Baru Village successfully implemented the ecovillage model in response to the 2015 flash flood disaster. The social movement led by the local community, with support from Non-Governmental Organizations and the Ministry of Environment and Forestry, managed 251 hectares of forest land. The active role of women as forest guards became an essential symbol of gender inclusivity in conservation. This study concludes that community-based social movements and government policy support are crucial in realizing sustainable tourism that benefits both the environment and society. The development of ecovillages, such as in Damaran Baru, demonstrates that environmental conservation and economic growth can coexist successfully. This study recommends enhancing tourist infrastructure, offering sustainable training programs for the local community, diversifying income streams, and establishing partnerships with external organizations to support long-term success.